Assessing the effects of partially replacing fishmeal with peanut meal on growth, body composition, digestibility and immunity in juvenile beluga (Huso huso) - Fatemeh Davoudi‐Sefidkohi; Abdolmohammad Abedian Kenari; Omid Safari (Journal of the World Aquaculture Society)
Abstract In this feeding trial, the replacement of fishmeal (FM) with peanut meal (PM) was examined to assess its effects on growth performance, body composition, digestibility, and immunity in cultured juvenile beluga (Huso huso; initial weight: 132 ± 8.5 g). Four experimental diets were tested (3 replicates; 12 fish each), including a control diet (0% replacement) and diets with 10%, 20%, and 30% PM replacement levels, fed to fish over a 56‐day period. The results showed that fish fed a diet with 10% PM replacement achieved the highest final weight, weight gain, and specific growth rate, as well as the lowest feed conversion ratio (FCR). As PM replacement levels increased, muscle protein content increased, while lipid content decreased (p < 0.05). Analysis of muscle fatty acids indicated that with higher replacement levels, saturated fatty acids (SFA) and polyunsaturated fatty acids (PUFAs) increased (p < 0.05), while highly unsaturated fatty acids (HUFAs) decreased (p < 0.05). Additionally, the 10% replacement treatment exhibited the highest levels of essential amino acids in muscle tissue (p < 0.05), along with the greatest digestibility of dry matter and crude protein (p < 0.05). Immune parameters, specifically lysozyme and ACH50, showed significant increases compared to the control as PM replacement levels rose (p < 0.05). Based on the results, it can be concluded that partial replacement of FM with PM at a level of around 10% can enhance growth performance, nutrient digestibility, and immune response in Juvenile beluga.